Review: Maternal health and the placental microbiome. (June 2017) - Pelzer, Elise; Gomez-Arango, Luisa F.; Barrett, Helen L.; Nitert, Marloes Dekker
Abstract: Over the past decade, the role of the microbiome in regulating metabolism, immune function and behavior in humans has become apparent. It has become clear that the placenta is not a sterile organ, but rather has its own endogenous microbiome. The composition of the placental microbiome is distinct from that of the vagina and has been reported to resemble the oral microbiome. Compared to the gut microbiome, the placental microbiome exhibits limited microbial diversity. This review will focus on the current understanding of the placental microbiota in normal healthy pregnancy and also in disease states including preterm birth, chorioamnionitis and maternal conditions such as obesity, gestational diabetes mellitus and preeclampsia. Factors known to alter the composition of the placental microbiota will be discussed in the final part of this review.